Leadership in education as the principal direction of educational policy - Machynska, Nataliіa (Educological discourse, 2022)
The article is devoted to the analysis of theoretical and practical aspects of educational leadership. It is noted that leadership is a model of management of an educational organization that stimulates the innovative behaviour of teachers, ensures the use of innovations at all levels of the organization. It should create the practice of corporate management in order to support the innovative behaviour of teachers at educational institutions of various types. It is shown by the author that one of the principal directions of the state educational policy is leadership in education as a way of effective staff management in the education management system. Various approaches to the definition of educational policy are proposed, where common indicators are: the organized and purposeful activity of the state; the complex system of measures of state institutions; the key subject of educational policy in society is the state; the education system is a leading institution of a democratic society. The priority areas of educational policy are highlighted: ensuring state guarantees of access to quality education; creation of conditions for improving the quality of general and vocational education; formation of effective economic relations in the education system; enrolling highly qualified specialists to the system of education, their support by the state and society; management of education development based on the distribution of responsibility between the subjects of the educational policy. The emphasis is placed on the technique of managing a structural unit at an educational institution (a set of operations, processes and procedures of managerial activity that are performed formally, based on rules and instructions). It has been proven that the training of managers in the main aspects of staff policy in the field of education, the involvement in training programs and advanced training in matters of staff management, contribute to the formation of scientifically based work with scientific and pedagogical staff, which ensures the effective organization of the educational process